A comparison of head motion and prefrontal haemodynamics during upright and recumbent cycling exercise. (27th April 2016) - Tempest, Gavin D.; Eston, Roger G.; Parfitt, Gaynor
Summary: The aim of this observational study was to compare head motion and prefrontal haemodynamics during exercise using three commercial cycling ergometers. Participants ( n = 12) completed an incremental exercise test to exhaustion during upright, recumbent and semi‐recumbent cycling. Head motion (using accelerometry), physiological data (oxygen uptake, end‐tidal carbon dioxide [PET CO2 ] and heart rate) and changes in prefrontal haemodynamics (oxygenation, deoxygenation and blood volume using near infrared spectroscopy [NIRS]) were recorded. Despite no difference in oxygen uptake and heart rate, head motion was higher and PET CO2 was lower during upright cycling at maximal exercise ( P <0·05). Analyses of covariance (covariates: head motion P >0·05; PET CO2, P <0·01) revealed that prefrontal oxygenation was higher during semi‐recumbent than recumbent cycling and deoxygenation and blood volume were higher during upright than recumbent and semi‐recumbent cycling (respectively; P <0·05). This work highlights the robustness of the utility of NIRS to head motion and describes the potential postural effects upon the prefrontal haemodynamic response during upright and recumbent cycling exercise.